17β‐Trenbolone exposure programs metabolic dysfunction in larval medaka. Issue 11 (4th June 2015) - Mizukami‐Murata, Satomi; Kishi‐Kadota, Katsuyuki; Nishida, Takashi
Abstract: Here, we used physiological and transcriptomic analyses to evaluate the effects of 17β‐trenbolone (TB) on metabolism during the early life stage of medaka ( Oryzias latipes ). In the physiological experiments, sex reversal rates increased continuously in proportion to TB concentrations (2–100 ng/L), and were 100% (all males) in the 200 ng/L treatment group. TB caused a significant increase in the gonadosomatic index of females at concentrations of 60 and 100 ng/L. These females exhibited swollen abdomens and decreased egg production and fertility. Significant increases were observed in the body mass index of these females. TB caused decreased fertility in males at concentrations >20 ng/L, but no other effects were observed. In the transcriptomic (microarray) experiments, larvae were exposed to TB for up to 7 d. Analyses using the KEGG Orthology Database revealed that predominant categories of significantly upregulated genes included "lipid metabolism" and "metabolism of terpenoids and polyketides." Thirteen genes (including those for hydroxymethylglutaryl‐CoA synthase, cytoplasmic synthase, and lanosterol synthase) related to cholesterol biosynthesis via the mevalonate pathway were highlighted in these categories. Reverse transcriptase‐polymerase chain reaction analyses were consistent with the microarray results, in terms of the direction and magnitude of change to gene expression. Among the downregulated genes, angiopoietin‐like 4 and mitochondrial uncoupling protein 1, which are inversely correlated with obesity, were detected in the TB treatments. In conclusion, the results suggest that the exposure of females to TB during the early life stage may cause metabolic dysfunctions, including obesity and disrupted cholesterol synthesis. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1539–1551, 2016.